Personnel security system of nuclear power plants using machine learning for psychological, behavioral and social media activity analysis. - Neaz, Fabiha; Ahmed, Hasan Tawqir; Granthi, Marium Tasnuva; Saha, Shuvro Dev (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.